The evolution of the “harvest machinery” : why capture capacity has continued to expand in Norwegian fisheries - Johnsen, Jahn Petter (Marine Policy, 2005)
Controlling the expansion of capture capacity has been a major challenge for the fisheries management systems around the North Atlantic. Despite focused attempts to reduce this capacity in recent years in different jurisdictions, it has continued to expand. This chapter uses a case study of changes in Norwegian fisheries to help explain why this has happened. The article supports the replacement of the rational actor approach that is currently hegemonic within fisheries management by a relational approach to the analysis of capture capacity expansion. A relational approach offers new insights into the ways political, economic, and technological forces continue to fuel capacity expansion within fishing. By use of this approach the article describes how the harvest machinery comes into existence. Keywords: Fishery policy; Capture capacity expansion; Management models; Cod fisheries; Harvest machinery